Measurement of the branching fraction of the B0→D+s π−decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kopecná, Renata; et al. (The European physical journal. C, Particles and fields, 2021)
A branching fraction measurement of the $${B ^0} {→ }{D ^+_{s}} {{π } ^-} $$decay is presented using proton-proton collision data collected with the LHCb experiment, corresponding to an integrated luminosity of $$5.0\,\text {fb} ^{-1} $$. The branching fraction is found to be $${\mathcal {B}} ({B ^0} {→ }{D ^+_{s}} {{π } ^-} ) =(19.4 ± $$$$1.8± 1.3 ± 1.2)× 10^{-6}$$, where the first uncertainty is statistical, the second systematic and the third is due to the uncertainty on the $${B ^0} {→ }{D ^-} {{π } ^+} $$, $${D ^+_{s}} {→ }{K ^+} {K ^-} {{π } ^+} $$and $${D ^-} {→ }{K ^+} {{π } ^-} {{π } ^-} $$branching fractions. This is the most precise single measurement of this quantity to date. As this decay proceeds through a single amplitude involving a $$b{→ }u$$charged-current transition, the result provides information on non-factorisable strong interaction effects and the magnitude of the Cabibbo-Kobayashi-Maskawa matrix element $$V_{ub}$$. Additionally, the collision energy dependence of the hadronisation-fraction ratio $$f_s/f_d$$is measured through $${{\overline{B}} {}^0_{s}} {→ }{D ^+_{s}} {{π } ^-} $$and $${B ^0} {→ }{D ^-} {{π } ^+} $$decays.
Im Titel sind"+", "-" und "0" hochgestellt und "s" ist tiefgestellt
Gesehen am 21.06.2021